A review of the preclinical and clinical studies on the role of the gut microbiome in aging and neurodegenerative diseases and its modulation - Hashim, Haslin Madihah; Makpol, Suzana (Frontiers in Cellular Neuroscience, 2022)
As the world population ages, the burden of age-related health problems grows, creating a greater demand for new novel interventions for healthy aging. Advancing aging is related to a loss of beneficial mutualistic microbes in the gut microbiota caused by extrinsic and intrinsic factors such as diet, sedentary lifestyle, sleep deprivation, circadian rhythms, and oxidative stress, which emerge as essential elements in controlling and prolonging life expectancy of healthy aging. This condition is known as gut dysbiosis, and it affects normal brain function via the brain-gut microbiota (BGM) axis, which is a bidirectional link between the gastrointestinal tract (GIT) and the central nervous system (CNS) that leads to the emergence of brain disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and frontotemporal dementia (FTD). Here, we reviewed the role of the gut microbiome in aging and neurodegenerative diseases, as well as provided a comprehensive review of recent findings from preclinical and clinical studies to present an up-to-date overview of recent advances in developing strategies to modulate the intestinal microbiome by probiotic administration, dietary intervention, fecal microbiota transplantation (FMT), and physical activity to address the aging process and prevent neurodegenerative diseases. The findings of this review will provide researchers in the fields of aging and the gut microbiome design innovative studies that leverage results from preclinical and clinical studies to better understand the nuances of aging, gut microbiome, and neurodegenerative diseases.